Sirenomelia: A Case Report - Joserizal Serudji (Universitas Andalas, 2022)
Sirenomelia is an extremely rare anomaly, an incidence of 1 to 4.2 in 100,000 births, in which a newborn born with legs joined together featuring amermaid-like appearance (head and trunk like humans and tail like ﬁsh), and in most cases die shortly after birth. Gastrointestinal and urogenital anomalies and single umbilical artery are clinical outcome of this syndrome. There are two important hypotheses for pathogenesis of mermaidsyndrome: vitelline artery steal hypothesis and defective blastogenesis hypothesisThe cause of the sirenomelia is unknown, but there are some possible factors such as age younger than 20 years and older than 40 years in mother and exposure of fetus to teratogenics. Here, we introduced 39 year old mother’s ﬁrst neonate with Sirenomelia syndrome. The mother had gestational diabetes mellitus and neonate was born with single lower limb, ambiguous genitalia, and thumb anomalies, and 4 days after birth, the neonate dieddue to multiple anomalies and imperforated anus.